2020
DOI: 10.1111/dth.14573
|View full text |Cite
|
Sign up to set email alerts
|

Skin vascular lesions: A new therapeutic option with sequential laser‐assisted technique

Abstract: Treatment of skin unaesthetic vascular lesions is still suboptimal. In this article, we present a multicenter study evaluating the efficacy and safety of the sequential 755 nm Alexandrite and 1064 nm ND:YAG lasers for the treatment of acquired and congenital vascular lesions of the skin. A total of 171 patients were included in the study (141 female and 30 male), median age 38, skin type from I to IV. Numbers of patients categorized for treated disease: 22 spider angiomas, 67 facial telangiectasia/spider veins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…20 Furthermore, a recently published study has suggested that the sequential 755 nm Alexandrite and 1064 nm LP Nd:YAG lasers may be effective for treating diverse congenital and acquired vascular lesions of the skin. 25 Together, these results suggest that dual therapy is superior to single-module treatments. In addition, IPL and 1064-nm Nd:YAG laser have shown to be effective for treating inflammatory facial acne vulgaris, without significant differences between them.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…20 Furthermore, a recently published study has suggested that the sequential 755 nm Alexandrite and 1064 nm LP Nd:YAG lasers may be effective for treating diverse congenital and acquired vascular lesions of the skin. 25 Together, these results suggest that dual therapy is superior to single-module treatments. In addition, IPL and 1064-nm Nd:YAG laser have shown to be effective for treating inflammatory facial acne vulgaris, without significant differences between them.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, this dual‐wavelength therapy has provided better aesthetic outcomes in patients with facial telangiectasias than its components 20 . Furthermore, a recently published study has suggested that the sequential 755 nm Alexandrite and 1064 nm LP Nd:YAG lasers may be effective for treating diverse congenital and acquired vascular lesions of the skin 25 . Together, these results suggest that dual therapy is superior to single‐module treatments.…”
Section: Discussionmentioning
confidence: 98%